PEMANFAATAN DATA SATELIT UNTUK ANALISIS POTENSI GENANGAN DAN DAMPAK KERUSAKAN AKIBAT KENAIKAN MUKA AIR LAUT - Anggraini, Nanin; Trisakti, Bambang; Soesilo, Tri Edhi Budhi (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2012)
Increasing of ocean water volume caused sea level rise (SLR) that threatens the existence of small islands and coastal areas, such as North Jakarta. Besides the SLR, North Jakarta is also threatened by land subsidence. This study aims to predict the height of SLR in 2030 and to analyze the impact of SLR on the coastal areas of North Jakarta. The total height of SLR in 2030 was predicted using tidal data, land subsidence data, and SLR prediction by B2 scenario from the Intergovernmental Panel on Climate Change (IPCC). Potential inundation area due to SLR was estimated using Digital Elevation Model Shuttle Radar Topography Mission (DEM SRTM) X-C band with spatial resolution 30 m. The damage was analyzed by doing the overlay between the inundation areas with the land use information extracted from QuickBird data. The result shows that the SLR predictions in 2030 are 2.88 m caused by the tide, 2.28 m caused by the land subsidence, and 1.29 m caused by the B2 scenario IPCC. The total height of SLR prediction is 6.45 m. The potential damages of land use are dominated by urban area (1045 ha) and industrial area (563 ha). The most inundated areas are located in Penjaringan sub-district for urban (523 ha) and in Cilincing sub-district for industrial area (311 ha).